Evaluasi Program Tahfidz Al-Qur’an dengan Menggunakan Model Countenance Stake di SDIT Al Iman - Inu Aulia Arba; Iffat Bening Qhuru’in Ahmad; Ahmad Musyarofi; Siti Zahrotus Sania; Muhammad Fata Rayyan Ghafur; Hesti Kusumaningrum (Lembaga Pengembangan Kinerja Dosen, 2025)
The Al-Qur'an Tahfidz program at SDIT Al-Iman aims to equip students with Al-Qur'an reading and memorization skills. This study employs the Countenance Stake evaluation model to assess program effectiveness. Results indicate the program successfully achieved its objectives through structured planning, systematic monitoring, and tailored improvement measures. The program positively impacts students' confidence and Al-Qur'an reading abilities. Recommendations for enhancement include increased parental involvement, digital monitoring systems, technology-based learning methods, and teacher training.